Lipidation states orchestrate CLICK-III/CaMKIγ's stepwise association with Golgi and rafts-enriched membranes and specify its functional coupling to STEF-Rac1-dependent neurite extension - Ageta-Ishihara, Natsumi; Takemoto-Kimura, Sayaka; Kondo, Yayoi; Okamura, Michiko; Bito, Haruhiko (Frontiers in Cellular Neuroscience, 2023)
CLICK-III/CaMKIγ is a lipid-anchored neuronal isoform of multifunctional Ca2+/calmodulin-dependent protein kinases, which mediates BDNF-dependent dendritogenesis in cultured cortical neurons. We found that two distinct lipidation states of CaMKIγ, namely, prenylation and palmitoylation, controlled its association with detergent-resistant microdomains in the dendrites and were essential for its dendritogenic activity. However, the impact of each lipid modification on membrane targeting/trafficking and how it specifies functional coupling leading to polarized changes in neuronal morphology are not clear. Here, we show that prenylation induces membrane anchoring of CaMKIγ, permitting access to the Golgi apparatus, and a subsequent palmitoylation facilitates association with cholesterol-enriched lipid microdomains or lipid rafts, in particular at the Golgi. To specifically test the role of palmitoylated CaMKγ in neurite extension, we identified and took advantage of a cell system, PC12, which, unlike neurons, conveniently lacked CaMKIγ and was deficient in the activity-dependent release of a neuritogenic growth factor while possessing the ability to activate polarized rafts signaling for morphogenesis. This system allowed us to rigorously demonstrate that an activity-dependent, lipid rafts-restricted Rac activation leading to neuritogenesis could be functionally rescued by dually lipidated CaMKIγ expression, revealing that not only prenylation but also palmitoylation is essential for CaMKIγ to activate a compartmentalized STEF-Rac1 pathway. These results shed light on the significance of recruiting prenylated and palmitoylated CaMKIγ into the coalescing signalosomes at lipid rafts together with Rac1 and its specific GEF and STEF and forming a compartmentalized Ca2+ signaling pathway that underlies activity-dependent neuritogenesis and morphogenesis during axodendritic polarization critical for brain development and circuitogenesis.